ANALISIS PENGARUH MEDIA PEMBELAJARAN BERBASIS VIDEO ANIMASI CANVA PADA PEMBELAJARAN MEKANIKA TEKNIK - Ravino Indra Julio (ADISAM PUBLISHER, 2024)
This research examines the use of Canva-based animated video learning media as a tool to enhance students’ understanding of mechanical engineering concepts. Video-based learning media is a very suitable choice in the learning process as it can facilitate material understanding and capture students’ attention. Analysis of relevant research journals indicates that video- based learning media has the potential to improve learning outcomes, especially in achieving the minimum competency standards (MCS), as it is considered very engaging for students and can influence their learning activities. However, the use of this media also requires teachers’ high creativity in creating engaging content.